Diagnosis of portal hypertension by transabdominal ultrasound - Ahamed, Md Saad; Kabir, Shikha; Mohiuddin, AS; Chowdhury, Poritosh Kumar (Bangladesh Medical Journal Khulna, 2015)
Portal hypertension is pathologic increase in portal venous pressure, with diversion of portal blood to the systemic circulation. The study was directed to measure as well as to compare the diameters of splenic, superior mesenteric and portal veins with their variation with respiration in normal subjects and in patients with portal hypertension. An analytic type of cross-sectional study was conducted at Radiology and Imaging Department of BIRDEM, Shahbag, Dhaka for one year (2011-12) among purposively selected 59 study subjects with chronic liver disease and portal hypertension, and 45 individuals without liver disease. Transabdominal ultrasonograpy of hepatobiliary system was carried out using computed sonography system with multiple probes having multiple frequency depending on physical built of the subjects. The diameters of selected veins were measured in the course of expiration and deep inspiration. In all control subjects, diameter variations of splenic vein and superior mesenteric vein were noted in the phases of respiration, the diameters increased during deep inspiration and decreased during deep expiration mean diameter and standard deviation of splenic vein and superior mesenteric vein were 6.95 ± 1.75 mm and 8.77 ± 2.06 mm respectively and during expiration they were 4.45 ± 1.24 mm and 5.66 ± 1.41 mm respectively. The difference in deep inspiratory and expiratory diameters had high statistical significance (p<0.0001). Patients with portal hypertension diameter variation with breathing at the level of splenic and superior mesenteric veins was observed only in 5 (9.47%) cases. Diminished response of splenic and superior mesenteric veins with respiration in transabdominal ultrasonography is an indicator of portal hypertension. DOI: http://dx.doi.org/10.3329/bmjk.v47i1-2.22558 Bang Med J (Khulna) 2014; 47 : 21-24